The Mendedah muatan karakter dalam bahan ajar bahasa Indonesia berbasis teks dalam Kurikulum 2013 - Zabadi, Fairul (Universitas Tangerang Raya, 2024)
The implementation of text-based language learning in the 2013 Curriculum resulted in changes to teaching materials according to the learning stages. Apart from that, the teaching materials that are prepared will be more complete if they contain character values that become the basis for students' behavior. This research aims to uncover the teaching materials and character values contained in Indonesian language teaching materials. The approach used is descriptive qualitative with content analysis techniques. The research data is in the form of Indonesian language teaching materials and character values sourced from Indonesian as a Vehicle for Knowledge: Class VIII (2014). The results of the research show that Indonesian language teaching materials have been prepared based on text-based learning stages although they need sharpening in building context in Chapters III and V. In addition, 15 character values were found, namely tolerance, caring for the environment, love of the country, nationalism, creativity, discipline , honest, curious, hard working, religious, democratic, communicative, socially caring, independent, responsible. The fifteen character values are spread across each chapter and learning stage.